Beneath the invisible cloud - Gerster, Julia (Amfiteater (Ljubljana), 2019)
The Great East Japan Earthquake, tsunami and nuclear accident of 11 March 2011 were not the first disasters to hit Japan, but they became known as the worst catastrophe of the peninsula after World War II. Thousands of people had to find a way to deal with the trauma they experienced and pass on the lessons they learned. Many of the survivors turned to art and culture to cope with their experiences. Among these art forms is also kamishibai, Japanese paper theatre. This paper analyses how kamishibai was used after the disaster and argues that it became a tool to convey lessons learned and a coping mechanism for the survivors to deal with personal trauma and express their grief. Thus kamishibai dealing with the disaster does not fit into classical typologies of the paper theatre, but rather represents a hybrid of memorialisation practices and disaster risk education in the sense of classical educational kamishibai. For this reason, I propose the new term of memorialisation kamishibai (kataritsugi kamishibai) to highlight these distinct features.
Keywords: 11. marec; 3.11-; cunami; disaster risk education; great Japanese east earthquake; izobraževanje o nevarnostih (naravnih) nesreč; Japanese paper theatre; japonsko papirnato gledališče; kamishibai; kamišibaj; memorialisation; radiation; sevanje; spominjanje; tsunami; veliki potres na jugu Japonske